2013
DOI: 10.1111/jpc.12207
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of infrared thermometers in very low birth weight infants and impact on newborn behavioural states

Abstract: Temperature measurements taken with infrared thermometers demonstrated less disruption to preterm infants' behavioural state, however accuracy of devices varied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
3
12
2
Order By: Relevance
“…This may be due to the inevitable direct heating effect of these interventions on the skin. Our findings contrasted with Jarvis's, which showed good agreement in one TT device for neonates nursed on incubators . This could be due to differences in incubator settings such as temperature and humidity levels.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This may be due to the inevitable direct heating effect of these interventions on the skin. Our findings contrasted with Jarvis's, which showed good agreement in one TT device for neonates nursed on incubators . This could be due to differences in incubator settings such as temperature and humidity levels.…”
Section: Discussioncontrasting
confidence: 99%
“…For babies nursed on room air, TT temperatures were statistically higher than AT temperatures by 0.1 °C. This corroborates with the range of values reported by aforementioned studies helmed by Lee, Duran, Haddad and Jarvis (0.0, 0.1, 0.2 and 0.07–1.34 °C, respectively) . Good clinical agreeability was observed between TT and AT.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several recent studies have reported on the accuracy of noninvasive temperature measurement methods for children (3)(4)(5)(6)(7)(8), and the overall picture is that such methods can, at best, serve as an alternative with limited reliability to rectal temperature measurement. Even though rectal temperature, which determines the core temperature with high precision, is widely viewed as the gold standard for body temperature measurement (9), axillary temperature measurement is frequently used in practice as it is considered safe and convenient (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%